'You can't put your roots down': housing pathways, rental tenure and precarity in older age. Issue 8 (13th September 2020) - Bates, Laura; Kearns, Robin; Coleman, Tara; Wiles, Janine
Abstract: In light of housing affordability concerns, we examine older people's experiences of renting within a context of enduring home-ownership norms and aspirations. Adapting Clapham's housing pathways framework, we ask: How is rental tenure experienced by older people who have encountered precarity in their housing history? Drawing on interviews with 13 older tenants, we observe the uneasy relationship between tenure insecurity and housing quality, and tensions between choice and luck in experiences of renting in later life. Three pathways related to renting in older age were apparent: life-long renting; loss of homeownership through adversity; and deliberate decisions to transition to renting. We note that challenges encountered in current and previous housing situations lead to diverse narratives of precarity in later life. These precarious experiences can be exacerbated by intersecting uncertainties associated with health, financial and personal circumstances. Older tenants' housing pathways and experiences illuminate ways in which precarity can disrupt opportunities for ageing well and ageing in place.